Drought propagation in the Indus Basin and the importance of snow and glacier melt in drought mitigation - Lara J. van den Bos; Arthur F. Lutz; Hester Biemans; Sonu Khanal; Walter W. Immerzeel (Journal of Hydrology: Regional Studies)
Study region: Indus Basin Study focus: Meteorological droughts can result in hydrological and soil moisture droughts with severe consequences for food production. In the Indus basin there are strong upstream-downstream linkages and upstream droughts may have strong downstream impacts. This study identifies periods of meteorological, hydrological and soil moisture drought in the Indus Basin for the period 1981–2010, analyses drought propagation and evaluates the role of meltwater in mitigating drought. We used outputs from a cryosphere-hydrology model (SPHY) and a crop-hydrology model (LPJmL), analysed the Standardized Precipitation Evapotranspiration Index (SPEI), the Standardized Streamflow Index (SSI), Soil Moisture Anomaly Index (SMAI) and crop yield, which are used as drought indicators to identify periods of drought, analyse drought propagation and its impacts. New hydrological insights for the region: Propagation of meteorological drought to hydrological drought and hydrological drought to soil moisture drought shows varied patterns and lag times. There were slightly more periods of soil moisture drought when meltwater was not available than when meltwater was available for irrigation. Our results show that identifying the link between soil moisture drought and yield anomaly remains challenging due to differences in temporal resolution of the data. Nevertheless, the results highlight the critical role of meltwater in mitigating yield variability, especially in the more downstream areas. This provides insight into the potential consequences of future cryosphere degradation for food production in the future.